A study on sexual harassment in the workplace: looking at the law in Malaysia / Nor Hazwani Mohd Nor. - Mohd Nor, Nor Hazwani (2008)
A study was conducted to analyse the problem of sexual harassment in the workplace in Malaysia. The aim of the study is to promote the need to legislate the laws in Malaysia concerning of sexual harassment in the workplace in Malaysia. Its objective is to analysis the implementation of the Code of Practice in Prevention and Eradication of Sexual Harassment in the Workplace which was introduced by the Ministry of Human Resources. Further, it is to be discovered whether the Code of Practice is adequate in rectifying the sexual harassment complainants. Secondly, is to compare our laws with United States concerning sexual harassment complainants, to analyse whether Malaysian Legal System is outdated in redressing the issue of sexual harassment in the workplace compares to United States. A qualitative type of research had been done such as survey methodology was employed whereby modified questionnaire was been distributed to 30 employees in private sectors as well as semi- structure interviews, library research and internet research. Interviews have been carried out and data have been collected from the Ministry of Human Resource and All Women's Action Society. The data includes the types of sexual harassment and factors that lead to the sexual harassment in the workplace. The overall results show that the level of sexual harassment awareness among the employees is low. Various suggestions were also made to improve the working environment in Malaysia.